Differentiation of axon-related Schwann cells in vitro: II. Control of myelin formation by basal lamina - Eldridge, CF (J Neurosci, 1989)
Several recent observations suggest that Schwann cell (SC) differentiation, including myelin formation, is dependent upon the development of basal lamina which characteristically surrounds each axon-SC unit in peripheral nerve. This dependence can be tested in a neuron-SC culture system developed in our laboratory in which SC differentiation, including basal lamina formation and myelination, is faithfully reproduced. The use of serum-free, defined medium (DM) with this culture system allows axon-driven SC proliferation but not basal lamina formation or myelination. We previously demonstrated that ascorbic acid, in the presence of a nondialyzable serum factor(s), stimulates basal lamina assembly and myelin formation with similar dose- response relationships (Eldridge et al., 1987). We hypothesized that ascorbic acid acts to promote SC myelination indirectly, by enabling the assembly of basal lamina. We now provide support for this hypothesis by demonstrating the following. (1) Pepsin-resistant triple- helical collagen molecules were produced only by SCs grown in the presence of ascorbic acid, suggesting that triple-helical type IV collagen may mediate the effect of ascorbic acid on basal lamina formation. (2) The formation of myelin by oligodendrocytes, which myelinate axons in the CNS without the concomitant deposition of basal lamina, was little affected by ascorbic acid, suggesting that the biosynthesis and assembly of myelin per se does not require ascorbic acid. (3) The provision of exogenous basal lamina matrix to SCs grown with neurons in DM without ascorbic acid promoted control levels of myelination (and basal lamina formation); the provision of exogenous fibrillar collagen matrix did not. (4) Purified laminin promoted control levels of myelination in the absence of ascorbic acid, but purified type IV collagen and heparan sulfate proteoglycan (HSPG) did not. Laminin caused SCs to assemble basal lamina-like structures that contained not only laminin but also HSPG and non-triple-helical type IV collagen. Thus, several types of experiments demonstrate that SC myelin formation can be controlled by regulating the ability of the SC to assemble basal lamina, illustrating that acquisition of basal lamina is a crucial prefatory step for further SC differentiation.